Association between Hypovitaminosis D and Acquired Immunodeficiency Syndrome (Research, Society and Development, 2020)
To investigate in the literature or current knowledge about an association between vitamin D deficiency and Acquired Immunodeficiency Syndrome. This is an integrative literature review, carried out by searching for original articles, in Portuguese, Spanish and English indexed in the Pubmed, Lilacs and Scielo databases. 28 articles were retrieved, of which 28.6% (n = 8) were included in this review for reading the full text. He observed that the studies compiled, 100% (n = 8) demonstrated that the population, in general, has high levels of vitamin D, regardless of factors such as location, sex, age, presence of HIV or use of ART, the latter two being possible elements for the worsening of vitamin D, or that identify a double-track relationship between the disease and hypovitaminosis. It was concluded that there is a strong association between hypovitaminosis D and an acquired immunodeficiency syndrome (AIDS), usually potentiated or conditioned by intrinsic risk factors or lifestyle. In addition, there was an association between vitamin deficiency in patients and greater vulnerability to opportunistic diseases and, conversely, a reduction in infections, chronic diseases and mortality in HIV / AIDS patients with disease statistics D. This was the objective of the study. , associated correlations were also identified between the decrease in the number of CD4 T lymphocyte cells. In spite of this, the need to conduct more research that allows greater clarification on a thematic proposal is emphasized.